2011
DOI: 10.1210/jc.2011-0399
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Growth Hormone Treatment in Short Children with X-Linked Hypophosphatemic Rickets: Effects on Linear Growth and Body Disproportion

Abstract: The 3-yr GH treatment improved linear growth without progression of body disproportion in short children with XLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 48 publications
3
31
0
2
Order By: Relevance
“…The only randomized study by Zivicnjak et al . (39) showed significant improvement of linear growth (+1.1 height SDS) in eight patients treated with rGH out of 16 short (mean height SDS −3.3) prepubertal children with XLHR. Addition of rGH induces a rise in mineral needs, which should be accompanied with a 20–30% increment in vitamin D analogs dosage.…”
Section: Therapy In Childrenmentioning
confidence: 91%
“…The only randomized study by Zivicnjak et al . (39) showed significant improvement of linear growth (+1.1 height SDS) in eight patients treated with rGH out of 16 short (mean height SDS −3.3) prepubertal children with XLHR. Addition of rGH induces a rise in mineral needs, which should be accompanied with a 20–30% increment in vitamin D analogs dosage.…”
Section: Therapy In Childrenmentioning
confidence: 91%
“…[21] A recent study has demonstrated the efficacy of GH in children with XLH where there was significant improvement in height SDS without worsening of skeletal disproportion. [22] Administration of single dose of calcitonin in XLH patients causes a significant and sustained drop in the circulating levels of FGF23 and an increase in the serum levels of phosphorus. [23] Short-term treatment with cinacalcet suppresses PTH, leading to increase in TMP/GFR and serum phosphate.…”
Section: X-linked Hypophosphatemic Ricketsmentioning
confidence: 99%
“…Growth hormone has been used to treat short stature in children with XLH. However, despite apparent improved linear growth over 3 years in a randomized open‐label study of XLH patients, there was no significant difference in final adult height between those treated with growth hormone and controls . Interestingly, the randomized study excluded patients with severe leg deformities, meaning that we have no controlled trial data on the potential for benefit or harm in that group.…”
Section: Medical Therapy Of Fgf23‐mediated Skeletal Disordersmentioning
confidence: 97%